The Maturing Development of Gut Microbiota in Commercial Piglets during the Weaning Transition - Chen, Limei; Xu, Yuesong; Chen, Xiaoyu; Fang, Chao; Zhao, Liping; Chen, Feng (Frontiers in Microbiology, 2017)
Early weaned piglets are vulnerable to diarrhea because of weaning stress and immaturity of intestinal tract. Compelling evidence suggests that gut microbiota is vital to host health. However, it is not well understood on the composition and succession of piglet gut microbiota during the weaning transition. In our two trials, total 17 commercial piglets were studied in a pig farm in Jiangxi Province, China. Fresh feces were collected for four times (10 days before weaned, weaned day, 10 days after weaned, 21 days after weaned) by rectal massage. Fecal bacterial composition was assessed by 16S rRNA gene V3-V4 regions sequencing by Illumina Miseq platform. The results showed that the gut microbiota of piglets shifted quickly after weaned and reached relatively stable level in 10 days after weaned. The alpha diversity increased significantly with the age of piglets. The microbiota of suckling piglets was mainly represented by Fusobacterium, Lactobacillus, Bacteroides, Escherichia/Shigella and Megasphaera. This pattern contrasted with that of Clostridium sensu stricto, Roseburia, Paraprevotella, Clostridium XIVa and Blautia, which were major representative genera after weaned. In summary, we delineated the development of piglet gut microbiota during the weaning transition. This study helps us understand the maturing development of gut microbiota in commercial piglets.